The Geography of Race and Ethnicity Effects in Federal Sentencing: A Descriptive and Spatial Analysis - Kramer, Kelsey L. (Criminal justice and behavior, 2023)
Research has focused mainly on whether race and ethnicity influence sentencing outcomes. Much less attention, however, has been paid to where, geographically, disparities occur in the United States. Using the United States Sentencing Commission’s sentencing data from FY2015 to FY2019, we estimated the effects of race and ethnicity on sentencing outcomes across 90 U.S. districts. First, we examined whether race and ethnicity varied across districts. Then we mapped district-level racial and ethnic disparities across the United States. Finally, we examined whether district-level racial and ethnic disparities were spatially correlated, creating hot- or cold spots of disparity. Evidence suggests that disparities are not concentrated within specific regions of the United States and are not spatially correlated. Instead, racial and ethnic disparities seem to be somewhat dispersed geographically. Yet, disparities do seem to concentrate in a relatively small portion of U.S. districts.